Penerapan Motion Graphics Pada Media Edukasi Parenting Berbasis Android Dengan Pendekatan Material Design Guidelines Untuk Bekal Young Parents Dalam Mendidik Anak (UNIB Press, 2025)
This research focuses on developing Eduparent, an Android-based parenting education app designed to help young parents under 21 educate their children in the digital age. The app incorporates animated motion graphics and follows material design guidelines for an intuitive and engaging user experience. The Research and Development (R&D) method and the Multimedia Development Life Cycle (MDLC) model were used to ensure systematic and effective development. Eduparent offers parenting tutorials through materials, expert videos, and animations. A study conducted with 36 young parents in Lubuk Layang Village showed a significant increase in parenting understanding after using the app. The Wilcoxon signed-rank test revealed a significance value of 0.01, indicating a positive impact on parenting knowledge. Keywords: Material Design Guidelines, Young Parents, Parenting, EduParent, Motion Graphics, Education